2020
DOI: 10.1002/ceat.202000071
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Fluid Catalytic Cracking Unit Performance on H‐Oil Severity, Catalyst Activity, and Coke Selectivity

Abstract: The effect of the quality of ebullated bed vacuum residue H-Oil hydrocracking gas oils cracked in a commercial fluid catalytic cracking unit (FCCU) on its performance was studied. Six different catalysts were employed in this study. Four catalysts were tested in a commercial FCCU, and two in a laboratory FCCU. An increase of the H-Oil hydrocracker reaction temperature was associated with a decrease in the K W factor of the H-Oil gas oils. The diminished K W factor of H-Oil gas oils resulted in lower FCCU conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 12 publications
(18 reference statements)
0
11
0
Order By: Relevance
“…Moreover, to the best of the authors' knowledge, there are no reports concerning the FCC performance during processing ebullated‐bed vacuum residue hydrocracking (EBVRHC) VGOs, which have different quality. The quality of the EBVRHC VGOs can be affected from the different crudes processed, from the different severity in the EBVRHC, and from the processing of different amounts of FCC slurry oil along with straight run vacuum residua in the EBVRHC 2, 12, 13.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, to the best of the authors' knowledge, there are no reports concerning the FCC performance during processing ebullated‐bed vacuum residue hydrocracking (EBVRHC) VGOs, which have different quality. The quality of the EBVRHC VGOs can be affected from the different crudes processed, from the different severity in the EBVRHC, and from the processing of different amounts of FCC slurry oil along with straight run vacuum residua in the EBVRHC 2, 12, 13.…”
Section: Introductionmentioning
confidence: 99%
“…The experience in the performance of LUKOIL Neftohim Burgas (LNB) commercial FCC unit (FCCU) has shown that the increase of the content of H‐oil VGO in the FCCU feed and the increase of severity of the H‐oil EBVRHC decreases the VGO conversion in the FCC unit 12. It has also proved that the increase of FCC slurry oil in the H‐oil vacuum residue feed blend negatively influences the FCC conversion 13.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since its introduction in 1942, fluid catalytic cracking (FCC) has become the main driver for oil refining performance improvement. , Over the years, it was found that FCC is a versatile process that can convert feeds of different originsvacuum oils, residual oils, crude oil, scrap tires pyrolysis oil, polyethylene plastic waste, biomass derived oilsinto high value transportation fuels and light olefin feeds for the petrochemical industry. Among all independent variables which affect the FCC unit (FCCU) performance, the feedstock quality has the biggest impact. While the processing of straight run vacuum gas oils (SRVGOs) in the FCCU is much more straightforward, the processing of secondary gas oils (from coker, visbreaker, and residue hydrocracker) is more challenging . Secondary gas oils are indeed characterized by a higher basic nitrogen content and by a higher level of refractory condensed aromatic compounds. The performance of the FCCU is therefore strictly correlated to the amount and the quality of the secondary gas oil fraction present in the FCC feed blend. , …”
Section: Introductionmentioning
confidence: 99%
“…More information about the ebullated bed VR hydrocracking technology can be found in the literature. , About one third of the products of the H-Oil hydrocracker presents vacuum gas oil (VGO) whose quality variation depends on VR hydrocracking severity and the amount of processed FCC slurry oil (SLO) in the H-Oil feed blend. ,, The LNB H-Oil VGO consists of three streams: heavy atmospheric gas oil (HAGO), light vacuum gas oil (LVGO), and heavy vacuum gas oil (HVGO). The H-Oil VGO processing at the LNB FCCU consists of HAGO20%; LVGO30%; and HVGO50% with the HVGO being the most problematic to the process . The catalyst Δ coke that the LNB FCCU can tolerate is maximum 0.64 wt %.…”
Section: Introductionmentioning
confidence: 99%